Rasa Syukur Menjadi Penyembuh: Perspektif Orang Tua Dari Anak Penyintas Kanker - Dewi, Lharasati; Rindiyani, Putri; Masdina, Dina; Masniati, Syafirah; Anjani, Rika; Rusdi, Huriyah Huwaidah (Al-Ijtimā': Jurnal Pengabdian Kepada Masyarakat, 2025)
Abstrack: This research shows the role of gratitude as the most important part for parents who have childern with cancer. This research used a participatory approach, 10 parents from the children’s cancer orphanage in Balikpapan, Indonesia were interviewed. Participants shared their experiences in caring for children with cancer and how cultivating a sens of gratitude helped them overcome the challenges with cancer. Researchers reveal that gratitude acts as asource of mental healt. Parents will find meaning in their experiences, overcome emotional stress, and improve well being. Gratitude also facilitates social connections and strengthens their support network. These results underscore the importance of gratitude for parents of childern with cancer, and show that incereasing gratitude can promote their happines in overcoming diffculties.